Using next generation sequencing to tackle non-typhoidal Salmonella infections - Wain, John; Keddy, Karen H; Hendriksen, Rene S; Rubino, Salvatore (The Journal of Infection in Developing Countries, 2013)
The publication of studies using next generation sequencing to analyse large numbers of bacterial isolates from global epidemics is transforming microbiology, epidemiology and public health. The emergence of multidrug resistant Salmonella Typhimurium ST313 is one example. While the epidemiology in Africa appears to be human-to-human spread and the association with invasive disease almost absolute, more needs to be done to exclude the possibility of animal reservoirs and to transfer the ability to track all Salmonella infections to the laboratories in the front line. In this mini-review we summarise what is currently known about non-typhoidal Salmonella in sub-Saharan Africa and discuss some of the issues which remain.